A Study on the Influence of Interactivity on Behavior Intention in Platform B2C Model. (17th November 2022) - Sun, Hao
Abstract : The progress of information technology and the popularity of the Internet have led to the rapid development of the network economy, and as a new shopping method, online shopping is gradually accepted and respected by consumers. With the development and maturity of online shopping market, the concept of consumers has also been changing, gradually changing from "panning for cheap" and "panning for convenience" to "panning for quality, " paying more attention to the quality of goods and services. B2C is more trusted by consumers than C2C in terms of reputation and quality assurance, so it has gradually become a hot spot in online shopping. With the popularization of online shopping, the development of e-commerce is increasingly characterized by the platform, and it is more and more difficult for shopping websites to attract online consumers with rich product information and functions alone. Using college students with online shopping experience in T-mall as the research subjects, descriptive analysis, exploratory factor analysis, correlation analysis, and regression analysis were used to study the influence of interactivity on customers' behavioral intention under the platform-based model from a perception perspective.